Hempcrete using Cement and Gypsum Plaster as a Binder - Khamput, Prachoom (Frontiers in Engineering Innovation Research, 2022)
This research aims to develop a lightweight concrete block product (hempcrete) using Portland cement and plaster gypsum plaster as a binder. The ratio of cement to gypsum plaster to fine sand to tap water equal 1: 1: 1: 1 by weight was kept in this experiment. The crushed hemp hurd was mixed through a 6 mm sieve at 0, 2, 4, 6, 8, and 10% of the total ingredients. The 15 x 15 x 15 cm hempcrete samples were mixed and formed, and the samples were cured for 7, 14, 21 and 28 days. Density, water absorption and compressive strength were investigated according to BS 1881: Part 108. The results showed that the hemp hurd was mixed in larger quantities, the density and compressive strength tended to decrease while the water absorption tended to increase accordingly. The amount of 6% by weight of hemp hurd is suitable for mixing with hempcrete size 10 x 20 x 60 cm according to TIS 2601-2556, which has a compressive strength of 37.45 kg/cm2, water absorption was 22.45%, and density was 1,137.19 kg/m3. It was classified as lightweight concrete block type C12. The hempcrete products obtained from this research can be used as lightweight blocks for building walls and can be plastered with normal plaster.